The Impact Of Empowerment On Organizational Citizenship Behavior (OCB) Through Job Satisfaction At The Medan City Land Office - Silvia Anggri Novira; Sunaryo (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to determine the effect of empowerment on Organizational Citizenship Behavior (OCB) through job satisfaction among employees at the Land Office of Medan City. This research uses a quantitative approach with an associative method. The population consists of 162 employees, including civil servants (PNS), government contract workers (PPPK), and non-permanent employees (PPNPN). Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) technique. The results show that: (1) empowerment has a positive and significant effect on OCB; (2) empowerment has a positive and significant effect on job satisfaction; (3) job satisfaction has a positive and significant effect on OCB; and (4) job satisfaction significantly mediates the relationship between empowerment and OCB. These findings indicate that higher levels of employee empowerment lead to greater job satisfaction, which in turn enhances Organizational Citizenship Behavior. Therefore, the management of the Medan City Land Office is encouraged to strengthen empowerment practices and maintain employee satisfaction through open communication, fair reward systems, and a supportive work environment to promote positive extra-role behaviors among employees.